Дослідження впливу конструкцій захоплювальних пристроїв на динаміку роботи лінійних двигунів у мехатронних модулях переміщення упаковок - Якимчук, Микола Володимирович; Кривопляс-Володіна, Людмила Олександрівна; Мироненко, Світлана Михайлівна; Якимчук, Владислав Миколайович (My University, 2020)
У статті розглядається можливість використання слідкувальних електричних приводів лінійного переміщення в пакувальному обладнанні для виконання операцій лінійних переміщень упаковок з використанням різних конструкцій захоплювальних пристроїв. Встановлено, що основним фактором відхилення роботи системи керування мехатронним модулем з лінійним електродвигуном від номінального режиму роботи є пружні коливання захоплювальних пристроїв, які є причиною додаткових збурень. За результатами досліджень можливих способів протидії впливу пружних коливань на роботу мехатронного модуля з лінійним електродвигуном запропоновано встановлення додаткових елементів компенсації в конструкції захоплювальних пристроїв. Отримані результати доцільно використовувати для синтезу мехатронних модулів переміщення упаковок з використанням різних конструкційзахоплювальних пристроїв. The article considers the possibility of using electric tracers of linear motion in packing equipment to perform operations of displacements of packages using different designs of gripping devices. It is established that the main factor of output of the control system of the mechatronic module with a linear motor from a steady mode of operation is the elastic vibrations of gripping devices with packaged food products, which together form additional perturbations. The obtained experimental harmonic graphs showed that the value of maximum acceleration is a component of the characteristics of inertial and driving forces and significantly affect the quality of implementation of a given law of motion. It has been investigated that the control system operates without fail when the amplitude of the first harmonic is greater than the amplitude of all others, that is, when the driving force is greater than the inertia force. As soon as the amplitude of any of the other harmonics becomes greater than the amplitude of the first, that is, the inertial component increases, the control system begins to respond to such perturbation. An attempt is made to control the “model-observerˮ to compensate for the action of inertia, which leads to the appearance of additional self-oscillations. As a result of the imposition of external oscillations on the internal oscillations, they accumulate and become non-attenuating. According to the results of experimental studies, a mathematical and statistical model of determining the time of the process of raising and lowering the structural elements of group packing by a mechatronic module with a linear motor was obtained. According to the results of studies of possible ways of counteracting the influence of elastic vibrations on the operation of a mechatronic module with a linear motor, it is proposed to limit their influence by establishing additional elements of compensation in the design of gripping devices. The results obtained can be used to design mechatronic modules for moving packages using different designs of gripping devices.
Keywords: кафедра мехатроніки та пакувальної техніки; двигун лінійний; linear motor; мехатронний модуль; mechatronic module; важіль; lever; комбінований захват; combined gripper